Mapping of MAC Address with Moving WiFi Scanner - Hidayat, Arief; Terabe, Shintaro; Yaginuma, Hideki (International Journal of Artificial Intelligence Research, 2017)
Recently, Wifi is one of the most useful technologies that can be used for detecting and counting MAC Address. This paper described using of WiFi scanner which carried out seven times circulated the bus. The method used WiFi and GPS are to counting MAC address as raw data from the pedestrian smartphone, bus passenger or WiFi devices near from the bus as long as the bus going around the route. There are seven processes to make map WiFi data.